Modeling of interfaces in two-dimensional problems using solid finite elements with high aspect ratio - Manzoli, O. L. [UNESP]; Gamino, Andre L. [UNESP]; Rodrigues, E. A. [UNESP]; Claro, G. K. S. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
The use of standard solid finite elements with a very high aspect ratio is proposed to model the behavior of thin interface regions between distinct components of composite structural members. It is shown that these elements present the same kinematics as the Continuous Strong Discontinuity Approach (CSDA) and can be used to describe bond stresses between components, even when the thickness of the interface region tends to zero. A scalar damage model consistent with the CSDA is presented to describe bond degradation due to slip. The technique is successfully applied to model the bond-slip behavior of reinforcing bars embedded in concrete. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Interface model; Finite elements; Bond-slip; Strong discontinuity; Reinforced concrete; Damage model